EFFECT OF SEEDING RATE AND SOME HERBICIDES ON GROWTH AND YIELD OF LENTOL Lens culinaric L MEDIC AND ACCOMPANYING WEEDS - Salim Hommadi Antar (Mesopotamia Journal of Agriculture)
The experiment was carried out in as agricultural seasons (2010-2011) at two locations : Field crops Dept research station /college of Agric & forestry and Talkeef northern east of mosul . The study was included two factors , the effect of seeding rates with three leveles (80 , 100 , 120 kg / ha) and herbicides Bronamed (1500 g/ha a.i) Treflan (1152 m/ha a.i) and in mixture at the same concentrations and with cheek treatment . The data were analyse according to the RCBD . using Duncan test using seeding rate (120 kg) kg / ha led to a significant decrease in the numbers of narrow leaves for both location . with a value of (0.67) and (0.50 ) respectively . as compared with the seeding of (80) kg . No.wide leaves weed , No . branches . No. bots / plabt . yiwld of plant , weight of 1000 seeds ded not deffer when either using (80) or (120) kg/ha higher when using (120) kg/ha as compared with 100 kg/ha for both locations with higher values estimated (90.33 and (87) for both location respectively . The seeding rate 100 kg were higher values (98.1) and (102.58) for both location respectively as compared with (80) kg / ha. The Bronamed and treflan and when they mixed together let to a significantly decrease in the numbers of wide and narrow leaves and there dry weight , plabt hight , No. mean and secondry branches and yield of plant and the weight of (1000) seeds as compared with the control treatment for both location , bronamd herbicide was superior in the total yield ( 8280 kg/ha) for the college as compared with the all other treatments were as the mixture between these two herbicides showed higher production at talkef location (817.78) kg/ ha .